The effect of adopting social responsibility in improving the reputation of the bank: An applied study of a sample of Jordanian banks - Zaki Hameed, Hawraa; makki Mahmood, Zainab; K. Jawad, Kamal (Iraqi Journal for Administrative Sciences, 2024)
The research aims to show how social responsibility and its role in improving the reputation of the bank in some Jordanian and Canadian banks and to come up with results and recommendations that help the Iraqi bank management to realize the nature of the relationship between the components of social responsibility and reputation in Jordanian banks, the research sample. The community of this research was represented by the Jordanian banks listed on the stock exchange, while the research sample was represented by seven Jordanian banks. and the main reason for choosing is because of the availability of digital data for social responsibility in The financial statements explicitly, As for the duration of the research, it was fifteen years for the period (2005-2019), according to what was available from the annual reports of the banks of the research sample.